Gambaran Faktor-Faktor Penyebab Terjadinya Kerusakan Fisik Dokumen Rekam Medis di Rumah Sakit Elisabeth Medan Tahun 2022 - Nasipta Ginting; Jev Boris; Desnata Evariani Zega (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2024)
Medical record is a document that contains patient identity data, examination, treatment given to patients. Factors for damage to medical record documents can be caused by intrinsic damage, meaning that damage that can occur comes from the object itself and extrinsic factors are the cause of document damage caused from outside the archive object. The research objective was to describe the factors that influence damage to medical record documents at Elisabeth Hospital Medan in 2022. The research design uses descriptive analysis which explains and also describes the characteristics of each variable. The population in the study was 59,956 medical record documents. The sampling technique used systematic random sampling, in order to obtain a sample for this study, namely 100 medical record documents taken from January to December 2022. The results of the research paper quality were mostly (78%) good and a small portion (22%) were not good. Most of the ink quality (64%) is good and a few (36%) is not good. The adhesive quality is almost entirely (99%) good and a small portion (1%) is not good. Extrinsic damage includes: judging from the physical factors, most of them (59%) are good and there are a few (41%) that are not good. All biological and chemical factors are good (100%) and there is no biological or chemical damage. Suggestions for research conducted by researchers at the Elisabeth Hospital in Medan are expected to provide new knowledge and information about document damage found in the medical record storage room.